Trochanteric femoral nonunion in patients aged over 60 years treated with dynamic condylar screw. Issue 2 (February 2020) - Lotzien, Sebastian; Rosteius, Thomas; Rausch, Valentin; Schildhauer, Thomas Armin; Geßmann, Jan
Highlights: Information about success rate and outcome for salvage procedures of trochanteric femoral nonunions are limited. Most of the existing studies included younger patients with different types of index procedures each chosen at the discretion of the surgeon. The highlights of this study are the homogeneous patient cohort and the number of included patients: the study includes 21 patients with aseptic femoral trochanteric nonunions aged over 60 years. All patients were treated with a standardized treatment procedure. Abstract: Introduction: Nonunions of trochanteric femoral fractures are uncommon due to a good blood supply of the cancellous bone of the trochanteric region. Nevertheless, if a nonunion occurs, complex revision procedures usually become necessary. The purpose of this study was to evaluate a series of aseptic trochanteric nonunions in patients aged 60 years or older, looking at outcomes regarding healing rate, implant-related complications and secondary surgeries. Material and Methods: We conducted a retrospective chart review of patients with aseptic femoral trochanteric nonunions aged over 60 years. Nonunion treatment consisted of implant removal, debridement of the nonunion, and restoration of the neck shaft angle, followed by DCS plating. An additional 4.5-mm limited contact dynamic compression plate was placed in twelve patients anteriorly. The primary outcome measure was bony healing and time to healing in months. Secondary outcome measures included postoperative complications related to the index procedure, range of motion of the affected hip and postoperative mobility. Results: A total of 21 patients with a mean age of 69.1 years met the inclusion criteria. After a mean follow-up of 21.62 months, 17 of the 21 nonunions healed successfully. The mean healing time was 6.59 months. A total of six of the 21 patients needed secondary revision surgery. At the final follow-up, a full range of motion of the hip was seen in 17 of the 21 hips. Conclusions: DCS treatment and preservation of the patient's femoral head can be successful for patients aged over 60 years with a well-preserved femoral head and acetabulum. However, preservation of the hip joint and revision plating might be associated with higher revision rates.